Real-Time Data Processing and Analytics in IoT Cloud Computing Systems - Manikandan, T.; Kumar S, Satheesh; Muruganandham, A.; Karthikeya, S.; Iqbal, J L Mazher (2024 Second International Conference Computational and Characterization Techniques in Engineering & Sciences (IC3TES), 2024)
From the cloud computing systems perspective, IoT real-time data analytics plays a major role in innovation boost and the value creation of a number of industries. This paper proposes a method for operations of real-time analytics in the internet of things cloud configurations with the background of data collection, ingestion, processing, analysis, and visualization. Adoption of intelligent technologies like machine learning, edge computing, and cloud-native architectures, the algorithm will easily transform the raw data from IoT streams into real-time actionable insights for the organizations. Having a system in order with a methodical approach, which includes identifying data sources, query processing, and scalability evaluation enables organizations to design and implement robust, resilient and cost-effective real time analytics ones that are tailor-made to suit the unique requirements of the organization. Through the value-based analysis, the key role of an immediate glimpse depicting process improvement, better decision making, and profit generation as well as customer experience perfection are emphasized. While robust uses the word that meshes several key ideas and has a negative connotation privacy and security measures aim for data integrity, confidentiality, compliance, and data protection against possible risks and liabilities (as criticism, protection, or a plan). The creation of an environment where people think innovatively and collaborate with each other and have the ability to review and build on their performance can be done with the help of the real-time data analytics. This can drive the businesses to sustainable growth and success in the digital era.